Obznanenye — catalogue of Novosel’s bookstore in Zagreb (1800/1801) (Libellarium: journal for research in the field of information and related sciences, 2009)
The reprint of Obznanenye, catalogue of Novosel’s bookstore in Zagreb printed in 1800 or 1801, is published in this issue of Libellarium as a supplement to Marijana Tomić’s contribution “Library catalogues as resources for book history: case study of Novosel’s bookstore in Zagreb (1794 — 1825)”. The original of this reprint is preserved in National Szechenyi Library (Országos Széchényi Könyvtár) in Budapest.
Keywords: Obznanenye; Novosel’s bookstore; reprint; National Szechenyi Library